Competitive Advantage And Sustainable Tourism Balkondes At Borobudur Area Magelang Regency - Achsa, Andhatu; Verawati, Dian Marlina; Destiningsih, Rian; Novitaningtyas, Ivo (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
The phenomena of stagnant tourists’ visits at Balkondes is the background why this study is carried out will lead to the shortage of people’s revenue. It is proposed to identify the competitiveness of Balkondes tourism in Borobudur Area, Magelang Regency with the approach of Porter’s Diamond and to formulate the sustainable tourism strategy with SWOT. Data collection employs structured interview with technique of informant determination by using the combination of quota sampling technique and accidental sampling technique with 200 respondents. The research result indicates the correlation and mutual support between each main component of Porter’s Diamond as well as the main component with supporting factors. As resulted by SWOT analysis, Balkondes has Strength and Opportunities that could be optimized as a strategy to sustain the tourism, on the other hand, the existence of Weakness and Threats could obstruct the sustainability of Balkondes tourism in Borobudur Area Magelang Regency.